A new Late Ordovician microdomatid gastropod genus from Seville, south west Spain, with a revision of Ordovician Microdomatoidea - Frýda, Jiri; Rohr, David M.; Robardet, M.; Gutiérrez-Marco, J. C. (Alcheringa: An Australasian Journal of Palaeontology, 2001)
11 páginas. A new microdomatid gastropod, Eopagodea sevillana gen. and sp. nov., is described from the Late Ordovician (pre-Hirnantian Ashgill) limestones of Seville, Ossa Morena Zone, Spain. Palaeozoic microdomatids lived in shallow-water environments and were restricted to warm-water regions. Occurrence of microdomatid gastropods in the pre-Hirnantian Ashgill limestones of the Cerrn del Hornillo syncline (Ossa Morena Zone, Spain) is interpreted as an example of an influx of warm-water faunal elements into the otherwise cool to cold climate of the Mediterranean region during a short-termed, pre-Hirnantian increase of palaeotemperatures. The Late Ordovician microdomatid genus Daidia Wilson, 1951, is revised and two new Late Ordovician (Ashgill) subspecies of Daidia cerithioides (Salter, 1859) are described: Daidia cerithioides sewardensis n. subsp. from the Don River area of the York Mountains, Seward Peninsula, western Alaska, and Daidia cerithioides wilsonae n. subsp. from the Little East Lake Formation of northwestern Maine. Peer reviewed